L. AUSTIN’S AND JOHN R. SEARLE’S CONCEPTION OF TRUTH - P. Alpár GERGELY (Studia Universitatis Babeș-Bolyai. Philosophia, 2015)
John L. Austin’s and John R. Searle’s Conception of Truth. One of the oldest and most accepted theories of truth is the correspondence theory of truth. I argue that both John L. Austin and John R. Searle accept the correspondence theory of truth, and I present the theory accepted by them. I also present the implications of the acceptance of this theory of truth in relation to their philosophy of language.